Signaling and initial public offerings: The use and impact of the lockup period - Arthurs, Jonathan D.; Busenitz, Lowell W.; Hoskisson, Robert E.; Johnson, Richard A. (Journal of Business Venturing, 2009)
To reduce information asymmetries for potential investors considering investment in an IPO venture, owners can signal the firm's longer-term viability and quality in several ways. The lockup period, is one signal that can be offered. We investigated the lockup period of a sample of 640 ventures going through the IPO and find that a longer lockup period acts as a substitute signal to venture capital (VC) and prestigious underwriter backing. Furthermore, we find that ventures which have a going concern issue can reduce the amount of underpricing at the time of the IPO by accepting a longer lockup period.